2014
DOI: 10.7250/ste.2014.003
|View full text |Cite
|
Sign up to set email alerts
|

The Shielding of Inbound Radiofrequency Electromagnetic Fields at Workplaces

Abstract: Abstract. The emergence of new technologies and increased use of wireless voice and data transmissions has increased the human exposure to the radiofrequency (RF) electromagnetic fields (EMFs). Effective reduction measures of these fields have become more relevant in risk management at workplaces. Not only occupational health, but also counter-espionage and low electromagnetic interference are important arguments for RF EMF mitigation. This study investigates the most commonly used mitigation materials and met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…In the first step, engineering controls should be undertaken wherever possible to reduce the device emissions of the fields to acceptable levels (32). Limited studies were found about shielding design or provision for microwave radiation in the workplace (9). The most protective measures found for controlling non-ionizing radiation exposure at high frequency were administrative controls (32-41).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the first step, engineering controls should be undertaken wherever possible to reduce the device emissions of the fields to acceptable levels (32). Limited studies were found about shielding design or provision for microwave radiation in the workplace (9). The most protective measures found for controlling non-ionizing radiation exposure at high frequency were administrative controls (32-41).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, shielding is a superior method for the prevention of microwave exposure (1). Previously, limited shields, such as metal sheet and metal wire mesh, were used to reduce the intensity of microwaves in the workplaces to protect workers against microwave radiation (1,9).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, PMMs have a number of properties that cannot be achieved with solid materials; for example, they provide significant noise reduction [10], and light scattering [11]. They can also be used for damping dynamic force [12], filtering liquids and gases [13], and shielding electromagnetic fields [14]. PMMs are the simplest in terms of structure and implementation.…”
Section: Introductionmentioning
confidence: 99%